INTEGRATED LIBRARY SYSTEM UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN PERPUSTAKAAN DENGAN MENGGUNAKAN METODE ALGORITMA APRIORI (Studi Kasus: PERPUSTAKAAN KABUPATEN CIREBON): METODE ALGORITMA APRIORI - Alfi Nurfajiah; Tuti Hartati Mindara; Dita Rizki Amalia (Journal of Information Technology, 2021)
Cirebon Regency Library is one of the libraries that stands on Jl. Sunan Drajat No.9 Source. Where the library has improved its services through the provision of facilities and rooms that are very adequate. With the increase in book collections in the library, it would be great if you use a data mining system that functions to determine the data set as a process that can help in finding the books desired by library customers. The association rule technique using a priori algorithm can be used as a reference in finding out simultaneous borrowing in one transaction that occurs on one item. After determining that one item, testing is carried out whether it can meet the support standard which can be used as a minimum requirement then a rule is made in accordance with the confidance drinking standard, since 2020 the Library System in Cirebon Regency has used localhost which is an integrated library system in providing services to customers. One of the services provided is information that is needed centrally so that it can support decision makers what books are available for borrowing, what are the conditions for becoming a member, who is already a member. By using this system, we can see a pattern of borrowed books based on recommendations from librarians and can make arrangements in book storage in accordance with the patterns of information in book storage.